Impact of prehospital physician-led cardiopulmonary resuscitation on neurologically intact survival after out-of-hospital cardiac arrest: A nationwide population-based observational study. (March 2019) - Goto, Yoshikazu; Funada, Akira; Goto, Yumiko
Abstract: Aim: The impact of prehospital physician care for out-of-hospital cardiac arrest (OHCA) on long-term neurological outcome is unclear. We aimed to determine the association between emergency medical services (EMS) physician-led cardiopulmonary resuscitation (CPR) versus paramedic-led CPR and neurologically intact survival after OHCA. Methods: We assessed 613, 251 patients using All-Japan Utstein Registry data from 2011 to 2015 retrospectively. The main outcome measure was 1-month neurologically intact survival after OHCA, defined as Cerebral Performance Category 1 or 2 (CPC 1–2). Results: Before propensity score matching, the 1-month CPC 1–2 rate was significantly higher in EMS physician-led CPR than in paramedic-led CPR [5.7% (1114/19, 551) vs. 2.5% (14, 859/593, 700), P < 0.001; adjusted odds ratio (aOR), 1.50; 95% confidence interval (CI), 1.40–1.61]. After propensity score matching, EMS physician-led CPR showed more favourable neurological outcomes than paramedic-led CPR [6.0% (996/16, 612) vs. 4.6% (766/16, 612), P < 0.001; aOR, 1.44; 95% CI, 1.29–1.60]. In most subgroup analyses after matching, physician-led CPR had higher 1-month CPC 1–2 rates than paramedic-led CPR did; however, 1-month CPC 1–2 rates were similar between the two CPR configurations for patients aged <18 years (5.6% vs. 8.2%, P = 0.10; aOR, 0.82; 95% CI, 0.46–1.47) and those who received bystander defibrillation (26.3% vs. 21.5%; P = 0.10; aOR, 1.07; 95% CI, 0.74–1.53). Conclusion: Within the limitations of this retrospective observational research, EMS physician-led CPR for OHCA was associated with improved 1-month neurologically intact survival compared with paramedic-led CPR. However, neurologically intact survival was similar for patients aged <18 years and those receiving bystander defibrillation.